2020
DOI: 10.1186/s13018-020-01938-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two minimally invasive procedures for osteoporotic vertebral compression fractures with intravertebral cleft: a systematic review and meta-analysis

Abstract: Background A systematic review and meta-analysis to assess the pros and cons of percutaneous vertebroplasty (PVP) versus kyphoplasty (PKP) for osteoporotic vertebral compression fractures (OVCFs) with intravertebral cleft (IVC) including all available evidence from controlled trials. Methods Databases including Pubmed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wanfang Data were searched to identify relevant studies comparing PVP and PKP for OVCFs with IVC. The outcomes mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(88 reference statements)
1
5
0
Order By: Relevance
“…As compared to our pooled results, KP was associated with signi cantly longer operation time versus the VP, which is consistent with the latest meta-analysis by Hongyu Wei (26). One possible explanation is the need of more complex procedures with KP, such as the repeated establishment of expander channel on the pedicle.…”
Section: Discussionsupporting
confidence: 91%
“…As compared to our pooled results, KP was associated with signi cantly longer operation time versus the VP, which is consistent with the latest meta-analysis by Hongyu Wei (26). One possible explanation is the need of more complex procedures with KP, such as the repeated establishment of expander channel on the pedicle.…”
Section: Discussionsupporting
confidence: 91%
“…Both methods are safe and effective for the treatment of vertebral body compression, but neither are perfect. The PMMA hardens quickly and behaves as a cast [57,58], especially in patients with an IVC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis involving 7 RCTs (929 subjects) concluded that ZA in combination with PVP or PKP is a safe, effective, and comprehensive treatment for OVF [46,47]. The addition of ZA significantly improved the long-term analgesia and bone metabolism indices [including BMD, ÎČ-isomerized Cterminal telopeptide and N-terminal propeptide of type I collagen; and Nterminal molecular fragment levels].…”
Section: Is It Safe To Add Zoledronate (Za) To Pvp or Pkp?mentioning
confidence: 99%